Conflicts of interest in e‐cigarette research: A public good and public interest perspective. - Capps, Benjamin; Eijk, Yvette; Krahn, Timothy M. (Bioethics, 2020)
The tobacco industry's involvement in the electronic cigarette research that informs public health policy is controversial. On the one hand, some are concerned that their involvement presents conflicts of interest that bias research outputs and invalidate the policies that use them. On the other hand, some have argued that the tobacco industry may support valid research and contribute to the goals of public health, for instance, if the interests of the e‐cigarette industry could be part of a tobacco smoking cessation policy. We approach this debate from the ethical perspective of the public interest and the public good, considering how legitimate researchers can square their expert opinion with validating tobacco industry‐funded research, given the perfidy of the tobacco industry and paucity of robust, conclusive evidence on the public health impacts of liberalizing e‐cigarette use.